Neurochemical correlates of male polymorphism and alternative reproductive tactics in the Azorean rock-pool blenny, Parablennius parvicornis - Miranda, Jason (2012)
In the common Azorean rock-pool blenny, Parablennius parvicornis, males exhibit alternative reproductive morphologies: (1) larger males defend nest sites, provide parental care, have anal glands (involved in pheromone release), testicular glands, and low gonad:body weight ratio (GSI) and (2) smaller, younger, males do not defend nests, have reduced glands and high GSI. These smaller non-nesting males behave as satellites (associated with nests) or sneakers (moving among nests), attempting to achieve parasitic fertilizations via sperm competition. In non-mammals, arginine vasotocin (AVT) is a key hypothalamic peptide involved in the control of reproductive behavior and physiology, and several fish species that exhibit alternative male reproductive morphs show polymorphism in AVT brain chemistry. We conducted an immunocytochemical study to generate comparative data on this intertidal blenny. Our analysis showed no difference in AVT-immunoreactive cell number or size between the male morphs, which is consistent with studies on other fish, including blennies. The number of AVT cells was positively correlated to fish body mass, while cell size showed no such relation. If corrected for body mass, the smaller non-nesting males have significantly more cells than the large nesting males. Our data suggest that the size and number of forebrain AVT cells develops initially to allow for reproduction in the young non-nesting males and this pattern does not appear to change when males take on the nesting morphotype later in life. This result appears to be consistent in many fishes with alternative male morphotypes.